Analisis Determinan Faktor Tanda dan Gejala Infeksi Saluran Kemih pada Remaja Putri di SMA Negeri 2 Karangan Kabupaten Trenggalek - Mayta Sari Dwianggimawati (Universitas STRADA Indonesia, 2022)
Background: In Indonesia, the prevalence of urinary tract infections is still quite high. The high number of population and adolescents is important because adolescent girls are more at risk of experiencing health problems than adolescent boys. The purpose of this study was to analyze the inflence of personal hygiene with signs and symptoms of urinary tract infections among adolescent girls at Karangan Senior High School, Trenggalek Regency.Methods: This study used a cross sectional design. The population were 164 female students of Karangan Senior High School. Sample were 116 female students that reached by stratified random sampling technique. The independent variable was personal hygiene behavior, while the dependent variable was the signs and symptoms of urinary tract infections. Data were obtained by structured questionnaire and were analyzed by Logistic Regression test.Results: Respondents that had experienced with signs and symptoms of urinary tract infections were 33 female students (28.45%). There was no influence between age and signs and symptoms of urinary tract infection among adolescent girls at Karangan Senior High School (p value 0.223>0.05). There was a influence between personal hygiene and signs and symptoms of urinary tract infection among adolescent girls at Karangan Senior High School (p value 0.00<0.05, PR=9.762, 95%CI=2.762-34.498).Discussion: From this study it can be concluded that personal hygiene affects the signs and symptoms of urinary tract infection. Personal hygiene is very influential on the quality of health, especially young women who are more vulnerable.